2013
DOI: 10.1167/iovs.13-11732
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness in Childhood

Abstract: PURPOSE. We examined choroidal thickness (ChT) and its spatial distribution across the posterior pole in pediatric subjects with normal ocular health and minimal refractive error. METHODS.ChT was assessed using spectral domain optical coherence tomography (OCT) in 194 children aged 4 to 12 years, with spherical equivalent refractive errors between þ1.25 and À0.50 diopters sphere (DS). A series of OCT scans were collected, imaging the choroid along 4 radial scan lines centered on the fovea (each separated by 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
145
8
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(185 citation statements)
references
References 44 publications
26
145
8
6
Order By: Relevance
“…[15][16][17][18][19] Also, there is recent data on the hemodynamic effect of chemicals-sildenafil and nicotine-on choroid, obtained by OCT. 20,21 In our population of 160 patients aged 4-23 years, we found a mean SFCT of 308 mm with substantial variation between individuals, which was consistent with previous studies in adults. 4,22 Recent studies examining in vivo choroidal thickness with OCT in children have reported mean SFCT values of 348 mm (in 48 Korean children aged 4-10 years), 9 330 mm (in 194 children aged 4-12 years), 10 and 342 mm (in 174 children aged 3.5-15 years). 11 Among these studies, only Park et al reported a negative correlation between SFCT and age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19] Also, there is recent data on the hemodynamic effect of chemicals-sildenafil and nicotine-on choroid, obtained by OCT. 20,21 In our population of 160 patients aged 4-23 years, we found a mean SFCT of 308 mm with substantial variation between individuals, which was consistent with previous studies in adults. 4,22 Recent studies examining in vivo choroidal thickness with OCT in children have reported mean SFCT values of 348 mm (in 48 Korean children aged 4-10 years), 9 330 mm (in 194 children aged 4-12 years), 10 and 342 mm (in 174 children aged 3.5-15 years). 11 Among these studies, only Park et al reported a negative correlation between SFCT and age.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, although our understanding of choroidal characteristics has increased substantially in recent years, only a few reports to date have provided values for choroidal thickness in children. [9][10][11] Recently, an increase in choroidal thickness with age but an inverse correlation of choroidal thickness with AL was also reported in healthy children aged 3.5-14.9 years. 11 Improved evaluation of normal choroidal thicknesses during eye growth should assist in the diagnosis of choroidal abnormalities associated with eye disease, and also allow us to understand the differences in the choroid during normal eye growth and the development of refractive error.…”
Section: Introductionmentioning
confidence: 90%
“…It has been also reported that choroidal thickness increases during childhood and decreases during adulthood. 5,6 Accurately and automatically measuring choroidal thickness is therefore of great interest. Spectral-domain optical coherence tomography (SD-OCT) provides a cross-sectional, three-dimensional (3D), microscale depiction of ocular tissues 7 and clearly distinguishable retinal layers, as shown in Figure 1.…”
mentioning
confidence: 99%
“…Одна-ко Read и соавт. показали, что у детей 4-6 лет толщина хориоидеи достоверно меньше, чем у детей 7-9 лет [37]. При этом обе группы авторов сходятся во мнении, что профиль хориоидеи у детей значительно варьирует.…”
unclassified